Comparison of adrenalectomy with conservative treatment on mild autonomous cortisol secretion: a systematic review and meta-analysis - Khadembashiri, Mohamad Mehdi; Mohseni, Shahrzad; Harandi, Hamid; Pejman Sani, Mahnaz; Khadembashiri, Mohamad Amin; Atlasi, Rasha; SeyedAlinaghi, SeyedAhmad; Mohajeri- Tehrani, Mohammadreza; Larijani, Bagher (Frontiers in Endocrinology, 2024)
Objective This systematic review and meta-analysis was conducted to compare the benefits of adrenalectomy and conservative treatment for comorbidities associated with mild autonomous cortisol secretion (MACS) in patients diagnosed with MACS. Background MACS is the most common benign hormone-secreting functional adrenal incidentaloma. Overproduction of cortisol is observed in MACS patients, resulting in a variety of long-term health issues, including arterial hypertension (HTN), diabetes mellitus (DM), dyslipidemia, obesity, and osteoporosis; however, the classic clinical manifestations of Cushing’s syndrome (CS) are not present. Methods A systematic search was conducted using MEDLINE, Embase, Web of Sciences, and Scopus databases on December, 2023. Two reviewers independently extracted data and assessed the quality of the included articles. A meta-analysis was performed to compare the beneficial effects of adrenalectomy versus conservative management for MACS-related comorbidities. Results Fifteen articles were included in this study, which evaluated 933 MACS patients (384 Adrenalectomy and 501 Conservative treatment, and 48 excluded due to incomplete follow-up duration). MACS diagnosis criteria were different among the included articles. All studies, however, stated that there must be no overt CS symptoms. Meta-analysis demonstrates the overall advantage of adrenalectomy over conservative treatment for MACS-related comorbidities (Cohen’s d = -0.49, 95% CI [-0.64, -0.34], p = 0.00). Subgroup analysis indicated that the systolic blood pressure (pooled effect size = -0.81, 95% CI [-1.19, -0.42], p = 0.03), diastolic blood pressure (pooled effect size = -0.63, 95% CI [-1.05, -0.21], p = 0.01), and BMD (pooled effect size = -0.40, 95% CI [-0.73, -0.07], p = 0.02) were significantly in favor of adrenalectomy group rather than conservative treatment but no significant differences between the two treatment groups in other MACS-related comorbidities were reported. Conclusion Despite the limited and diverse data, this study demonstrates the advantage of adrenalectomy over conservative treatment for MACS-related comorbidities.